HLA-G and HLA-E specific mRNAs connote opposite prognostic significance in renal cell carcinoma - Kren Leos; Valkovsky Ivo; Dolezel Jan; Capak Ivo; Pacik Dalibor; Poprach Alexandr; Lakomy Radek; Redova Martina; Fabian Pavel; Krenova Zdenka; Slaby Ondrej (BMC, 2012)
Abstract Background Renal cell carcinoma (RCC) is characterized by its resistance to radiotherapy and/or chemotherapy. On the other hand, it is an immunogenic tumor - it is able to stimulate antitumor responses. A prognostic significance of HLA-G expression by neoplastic cells in RCC is not well characterized; significance HLA-E expression in RCC is not characterized at all. Methods In our study, we evaluated the expression of HLA-G and HLA-E specific mRNA transcripts produced by neoplastic cells in 38 cases of RCC and in 10 samples of normal kidney parenchyma. The results were statistically correlated with various clinico-pathological parameters. Results We confirmed that HLA-G is downregulated in normal kidney tissue; if it is up-regulated in RCC, then it is connected to worse prognosis. On the other hand, HLA-E mRNA transcripts were present in both normal kidney tissue and RCC and their increasing concentrations counterintuitively carried better prognosis, more favorable pT stage and lower nuclear Fuhrmann's grade. Conclusion Considering the fact that there is known aberrant activation of HLA-G and HLA-E expression by interferons, identification of HLA-G and HLA-E status could contribute to better selection of RCC patients who could possibly benefit from more tailored neoadjuvant biological/immunological therapy. Thus, these molecules could represent useful prognostic biomarkers in RCC, and the expression of both these molecules in RCC deserves further study. The virtual Slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/7383071387016614